Implementasi Wireless Application Protocol (WAP) untuk Layanan Pengisian KRS di Politama Surakarta - Agus Haryawan (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2013)
Course registration is a routine activity that is carried out every new semester. Along with the increasing number of students in Politama, the running computer and intranet system are no longer able to provide students for completing their registration activity. The Internet and WAP based course registration system provides a choice for students on registering courses via WAP mobile devices. This system is developed with waterfall process model. System analysis and design uses object-oriented method an MVC (Model View Controller) design pattern with UML (Unified Modelling Language) notation. System is directly tested with usability testing. There are five usability attribute to be tested, namely learnability, efficiency, memorability, errors, and satisfaction. Results show that this WAP-based system has good enough attribute values. All mean values are above 3 (easy), based on Likert scale 1 (very difficult) to 4 (very easy).